Accelerating structure with alternating-phase and permanent magnet focusing - Gussev, Ye.V.; Demchenko, P.A.; Shulika, N.G.; Shulika, O.N.; Zalesky, D.Yu. (Вопросы атомной науки и техники, 2014)
Proposed is the method for particle motion stability in linacs based on a combination of phase-alternating and longitudinal magnetic focusing using permanent magnets made of neodymium-iron-boron alloy. Presented are the results of the accelerating structure calculations.